Exploring the Interplay of Mental and Metabolic Factors in Erectile Dysfunction Management: A Case Report - Angellee, Jesselyn; Suharyani, Sally; Tanojo, Tjahjo Djojo; Pakpahan, Cennikon; William, William; Utomo, Natasha Susanto (Indonesian Andrology and Biomedical Journal, 2025)
Background: Erectile dysfunction (ED) affects 20-50% of men globally and considerably diminishes the patients’ and their partners’ quality of life. This condition has multifactorial causes, including depression and metabolic syndrome, resulting in a complicated interaction of physical and psychological components. Case: A man in his mid-twenties presented to the Andrology outpatient clinic at Dr. Soetomo General Hospital with a sudden onset of ED, reporting a decrease in his Erection Hardness Score (EHS) from 3-4 to 1 following penetration attempts. He had a history of childhood attention deficit hyperactivity disorder (ADHD) and recent unemployment, resulting in profound depression. Prior inconsistent treatments encompassed sertraline, fluvoxamine, and clobazam. Physical and laboratory examinations revealed metabolic syndrome. The patient was diagnosed with severe ED secondary to mixed etiology, class II obesity, major depressive episode, and metabolic syndrome. He received education on the diagnosis, possible underlying causes, and management options. Discussion: The case presented illustrates the intricate interplay between ED and comorbidities such as depression and metabolic syndrome. Depression exacerbates ED through hormonal dysregulation and reduced parasympathetic activity, while metabolic syndrome contributes to ED through endothelial dysfunction and nitric oxide (NO) depletion. Effective ED management requires a multidisciplinary approach, combining lifestyle modifications, psychological support, and pharmacological treatment. Tailored strategies addressing both physical and psychological aspects are essential for improving outcomes. Conclusion: Comprehensive and integrative care in managing ED, particularly when associated with complex comorbidities, is needed to enhance the patient’s erectile function and quality of life.